Symmetry Breaking-Induced Resonance Dynamics in Bloch Point Nanospheres: Unveiling Magnetic Volume Effects and Geometric Parameters for Advanced Applications in Magnetic Sensing and Spintronics - Escrig-Murua, J; Saavedra-Díaz, E (American Chemical Society, 2024)
This study explores the impact of symmetry breaking on the ferromagnetic resonance of Bloch point (BP) nanospheres. Through standard Fourier analysis, we unveil two distinct oscillation mode groups characterized by low and high frequencies, respectively. Our findings emphasize the pivotal role of magnetic volume in shaping resonance amplitudes, providing new insights into the intricate dynamics of BP states. The investigation of geometric parameters reveals a quasi-monotonic decrease in resonance frequencies as a function of the asymmetry degree attributed to symmetry-breaking induced by geometric modifications. Spatial distribution analysis showcases unique resonance frequencies for the upper and lower BP hemispheres, highlighting the nuanced impact of the geometry on mode excitation. As the radius increases, additional modes emerge, demonstrating a compelling relationship between the magnetic volume and frequency. Phase analysis unveils coherent oscillations within each BP hemisphere, offering valuable insights into the rotational directions of the excitation poles. Beyond fundamental understanding, our study opens avenues for innovative applications, suggesting the potential use of nanospheres in advanced magnetic sensing, data storage, and nanoscale spintronic devices. © 2024 American Chemical Society.